2015
DOI: 10.1371/journal.pone.0133520
|View full text |Cite
|
Sign up to set email alerts
|

Subtypes and Prognosis of Guillain-Barré Syndrome in Southwest China

Abstract: The proportion of different subtypes of Guillain-Barré syndrome (GBS) and their prognosis varied significantly among different regions. This study attempts to investigate the clinical subtypes and outcome of GBS in southwest China. Patients with GBS admitted to The First Affiliated Hospital of Chongqing Medical University from January 2006 to March 2013 were included in our study. Patients were classified into acute inflammatory demyelinating polyneuropathy (AIDP) group, acute motor axonal neuropathy (AMAN) gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
41
2
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 38 publications
9
41
2
5
Order By: Relevance
“…In previous studies, axonal subtype of GBS has been associated with poor outcome. However, our study did not find significant associations between axonal GBS and poor outcome irrespective of which electrodiagnostic criteria used.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In previous studies, axonal subtype of GBS has been associated with poor outcome. However, our study did not find significant associations between axonal GBS and poor outcome irrespective of which electrodiagnostic criteria used.…”
Section: Discussionmentioning
confidence: 85%
“…We also found that patients with MFS improved irrespective of immunotherapy, confirming findings from previous studies. 17,19 In previous studies, [20][21][22][23][24][25] axonal subtype of GBS has been associated with poor outcome. However, our study did not find significant associations between axonal GBS and poor outcome irrespective of which electrodiagnostic criteria used.…”
Section: Discussionmentioning
confidence: 97%
“…A number of studies have compared triggering events, clinical characteristics, and outcomes in AMAN and AIDP . Most of these studies, however, were based on adult populations or included both adults and children.…”
Section: Discussionmentioning
confidence: 99%
“…11,13 A number of studies have compared triggering events, clinical characteristics, and outcomes in AMAN and AIDP. 15,17,[30][31][32] Most of these studies, however, were based on adult populations or included both adults and children. Among the studies comparing triggering events in AMAN and AIDP in children, 1 study from Japan found an association of gastroenteritis and GM1 antibody with AMAN and cranial nerve palsy with AIDP.…”
Section: Discussionmentioning
confidence: 99%
“…However, these kinds of generalisations may ignore regional differences, particularly the genetic and environmental differences between South China and North China, and thus lead to somewhat incorrect assessments 12. For example, unlike the data from northern China, a single-centre research conducted in southwest China has revealed that AIDP was the most common subtype (up to 57%) 13. In addition to affecting an individual’s susceptibility to develop a specific subtype of GBS, regional differences may also influence the course and severity of disease 3.…”
Section: Introductionmentioning
confidence: 99%